2005
DOI: 10.1002/crat.200410336
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of Raman-active mode frequencies and linewidths in TlGaSe2 layered crystals

Abstract: Raman spectra of TlGaSe 2 crystal at different temperatures are discussed. The temperature dependence of frequency shifts and linewidths of the Raman peaks in the frequency region of 10-320 cm -1 have been measured in the range from 50 to 320 K. The analysis of the experimental data showed that the temperature dependencies of phonon frequencies and linewidths are well described by considering the contributions from thermal expansion and lattice anharmonicity. The anharmonic contribution (phonon-phonon coupling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
2
10
1
Order By: Relevance
“…However, they found that four‐phonon term is the dominant damping process in this material. This is in difference with the results of the present study as well as with reports for CuGaS 2 , AgGaS 2 , AgGaSe 2 , and TlGaSe 2 ternary semiconductors indicating that the phono–phonon coupling contribution is dominated by the cubic interactions (three‐phonon term) whereas four‐phonon coupling is less important in these materials.…”
Section: Resultscontrasting
confidence: 99%
“…However, they found that four‐phonon term is the dominant damping process in this material. This is in difference with the results of the present study as well as with reports for CuGaS 2 , AgGaS 2 , AgGaSe 2 , and TlGaSe 2 ternary semiconductors indicating that the phono–phonon coupling contribution is dominated by the cubic interactions (three‐phonon term) whereas four‐phonon coupling is less important in these materials.…”
Section: Resultscontrasting
confidence: 99%
“…The values of phonon frequencies (v i ) at P = 0 GPa along with results of other works [4,12,31] are given in Table 1. The recorded mode frequencies are in good agreement with the ones found in previous studies [4,12,31,32]. The lattice vibrational modes can be divided into two groups: intralayer modes, related to vibrations of Ga 4 Se 10 complexes, and low-frequency interlayer (Ag + 2Bg) modes, related to vibrations of thallium ions and Ga 4 Se 10 complexes.…”
Section: Resultssupporting
confidence: 89%
“…These properties make them useful as photo-sensitive devices [2]. In particular, ternary TlGaSe 2 has been object of different physical properties studies in Raman [3], electrical conductivity [4] and Hall effect [5], among others.…”
Section: Introductionmentioning
confidence: 99%